Practices of Poverty Measurement and Poverty Profile of Bangladesh - Faizuddin Ahmed (Asian Development Bank (ADB), 2004)
The present paper discusses the poverty measurement techniques being used in and the poverty profile of Bangladesh. Data used in the paper are mainly taken from two national surveys: Household Income and Expenditure Survey (HIES) and Poverty Monitoring Survey (PMS) conducted by Bangladesh Bureau of Statistics (BBS). Poverty in Bangladesh was earlier measured by direct calorie intake (DCI) method. The food energy intake (FEI) method was first used in the Poverty Monitoring Survey 1995. The cost of basic need (CBN) method was first used in HIES 1995-1996 and then in HIES-2000. Findings from the surveys indicate that the incidence of poverty has declined over the years. The Foster-Greer Thorbecke class of poverty estimates also indicate reduction of the poverty head count ratio, poverty gap, and squared poverty gap in the recent past. The distribution of income and expenditure shows that though nominal income has increased, income distribution has become skewed with high concentration of income in the highest decile and comparatively lower income share in the lowest decile. The quintile distribution of income also shows similar evidence. With respect to nonincome indicators, infant mortality rate has declined, life expectancy has increased, and enrollment in primary and secondary levels has increased.
hdl:11540/1911
Keywords: 330; Armut; Armutsbekämpfung; Messung; Bangladesch